2006
DOI: 10.1021/es060409+
|View full text |Cite
|
Sign up to set email alerts
|

Flesh Quality of Market-Size Farmed and Wild British Columbia Salmon

Abstract: This study compared the flesh quality of farmed and wild sources of British Columbia (BC) salmon with respect to concentrations of polychlorinated biphenyl compounds, polychlorinated dibenzodioxins/dibenzofurans and their associated toxic equivalents, total mercury (THg), methylmercury (MeHg), and selected fatty acids of known importance for human health viz., omega-3 (n-3) highly unsaturated fatty acids (n-3 HUFAs) and (n-6) fatty acids. Skinned fillets from known sources of farmed Atlantic, coho, and chinook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(110 citation statements)
references
References 23 publications
9
94
7
Order By: Relevance
“…Whether the cardio-protective omega-3 fatty acids in fish neutralize or markedly decrease the potential health risks associated with exposure to persistent organic pollutants is not known. There appears to be some consensus that regular fish consumption should be encouraged for its overwhelming cardioprotective properties [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the cardio-protective omega-3 fatty acids in fish neutralize or markedly decrease the potential health risks associated with exposure to persistent organic pollutants is not known. There appears to be some consensus that regular fish consumption should be encouraged for its overwhelming cardioprotective properties [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences in metal tissue concentrations were apparent between the two salmon species studied. Previous studies have shown that chinook salmon tend to exhibit higher Hg concentrations compared with other Pacific salmon species, in part because of their comparatively high trophic position [23].…”
Section: Trace Element Concentrationsmentioning
confidence: 99%
“…Analyses of organohalogens in salmon muscle and eggs samples were conducted at the Institute of Ocean Sciences (Sidney, BC, Canada). Procedures and quality assurance-quality control protocols employed for simultaneous extraction, cleanup, and quantification of multiple organohalogen contaminants (PCBs, PCDD/Fs, PBDEs, and OCPs) by gas chromatography-highresolution mass spectrometry (GC-HRMS) have been thoroughly detailed by Ikonomou and colleagues [22][23][24][25] 4 in a mortar, transferred quantitatively into an extraction column, and extracted with approximately 250 ml DCM/hexane (1:1 v/v). Thirty percent of the extract solution by weight was transferred into a 250-ml round-bottom flask.…”
Section: Sample Cleanup and Analysismentioning
confidence: 99%
See 2 more Smart Citations